Alih Kode dan Campur Kode dalam Keluarga Multibahasawan Perkawinan Indonesia- Perancis dalam Film “Liam Dan Laila” - Ladiva, Laviola Salsabilla; Juita, Novia (Persona: Kajian Bahasa dan Sastra, 2023)
The purpose of this research is to (1) Describe the types of code switching in the film Liam and Laila, (2) Describe the factors that cause code switching in the film Liam and Laila (3) Describe the types of code mixing in the film Liam and Laila, (4) Describe the factors that cause it to occur. code mixing in the film Liam and Laila. This research is included in the type of qualitative research with descriptive methods. The data for this research are dialogues in which there is code switching and code mixing. The data source for this research is the film script Liam and Laila (transcribed video) which contains dialogues from the characters. The data collection technique for this research is non-participant observation. Observations begin with (1) watching the film Liam and Laila, (2) record and transcribe the film recordings of Liam and Laila, (3) observe and analyze every dialogue that appears, (4) use the katat technique to collect every data obtained from the observations, (5) collect and record all the dialogue in which there are elements of code switching and code mixing to be explained further. The results of this research are. First, the type of code switching that occurs in the film Liam and Laila is divided into two, namely (1) external code switching which includes code switching from Indonesian to English and vice versa (2) internal code switching which includes code switching from Indonesian to English. Minangkabau and vice versa. Second, the types of code mixing are (1) outbound code mixing which includes code mixing in Indonesian and English (2) inward code mixing which includes code mixing in Indonesian and Minangkabau. The third factor that causes code switching includes (1) Speaker (2) Speech partner (3) Generating a sense of humor (4) Just being prestigious. The four factors that cause code mixing include (1) speaker factors (2) linguistic factors.